2007
DOI: 10.1007/s11144-007-5081-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of dimethyl ether to methanol over solid acids

Abstract: The hydration of dimethyl ether (DME) to methanol over various solid acids was studied. The acidity of the catalysts is determined by FTIR spectroscopy. The hydration is found to occur predominantly on the Brönsted acid sites. Among the catalysts studied, WO x /ZrO 2 and H-ZSM-5 appeared to be most active and selective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The Lewis acid/weak acid sites in DME carbonylation are inefficient to formation of MA. Hence, methanol, which can be formed at the initial induction stage by the reaction of DME with Bronsted acid sites (H + ) in/on zeolite, or the hydration of DME on Bronsted acid sites, , became the main byproduct. It is worth mentioning here that the H 2 O mainly comes from the carbon deposition reaction, but because of the limited mass transfer of zeolite channel and the quick conversion of carbon depositing precursors to hard carbons, most of the products of carbon deposition reaction cannot be detected by GC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The Lewis acid/weak acid sites in DME carbonylation are inefficient to formation of MA. Hence, methanol, which can be formed at the initial induction stage by the reaction of DME with Bronsted acid sites (H + ) in/on zeolite, or the hydration of DME on Bronsted acid sites, , became the main byproduct. It is worth mentioning here that the H 2 O mainly comes from the carbon deposition reaction, but because of the limited mass transfer of zeolite channel and the quick conversion of carbon depositing precursors to hard carbons, most of the products of carbon deposition reaction cannot be detected by GC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with the catalytic performance of the five MFI zeolites (Table 1). In the hydration of DME using MFI zeolites, no MeOH production was observed at 673 K due to thermodynamic disadvantages, although a high MeOH selectivity was reported at 473-573 K [26,27]. Magomedova et al reported that in the DTO reaction at 593 K, MeOH was selectively produced at <70% DME conversion in the alkene cycle [28].…”
Section: Screening Of Zeolitesmentioning
confidence: 99%
“…Recently, a WO x /ZrO 2 system was proved to be an active and selective catalyst for the DME hydration to methanol [25]. The catalyst provided the DME conversion close to the equilibrium value and 100% methanol selectivity in the temperature range of 200-300°C, GHSV = 10000 h -1 , and molar ratio H 2 O/DME = 3.…”
Section: Introductionmentioning
confidence: 99%
“…WO x /ZrO 2 was used as a solid-acid catalyst for the DME hydration. The synthesis and catalytic performance of WO x /ZrO 2 in the DME hydration to methanol are given in [25]. The commercial CuZnAlO x catalyst (chemical composition Cu : ZnO : Al 2 O 3 : Cr 2 O 3 = 38 : 28 : 33 : 1.5 wt.%, BET surface area 75 m 2 /g) was used as a catalyst for methanol SR. As special experiments showed, CuZnAlO x is an active and selective catalyst for the methanol SR at 230-300°C and appears to be completely inactive for both the DME SR and DME hydration at temperatures up to 360°C.…”
Section: Introductionmentioning
confidence: 99%